Analisis Sentimen Kenaikan Harga BBM pada Media Sosial Twitter - Iqbal Musyaffa; Mia Kamayani (Prosiding Seminar Nasional Teknoka, 2022)
Based on information in a press conference at the Merdeka Palace on Saturday, 03 September 2022 at 14.30 WIB, President Joko Widodo has decreed that the price of fuel be officially raised. This is a burden for road users, especially users of two-wheeled vehicles. Currently, many people use social media sites to submit complaints regarding this topic. One of them social media Twitter. Therefore, sentiment analysis was carried out using 2 methods, namely the Naïve Bayes Classifier and the Decision Tree on 1100 tweets obtained from the keyword "bbm up". The test results show thatthe best Performance is using the Naïve Bayes Classifier algorithm, which produces values with an accuracy of 94.91%and for the Decision Tree algorithm only gets an accuracy of 62.57%. The results of sentiment are, positive totaling 68data, neutral totaling 20 data, and negative totaling 301 data. The results of more negative sentiment show that the increase in fuel prices in Indonesia has not been accepted by the Indonesian people on social media Twitter.